Weed dynamics on Amazonian Dark Earth and adjacent soils of Brazil - Major, Julie; DiTommaso, Antonio; Lehmann, Johannes; Falcão, Newton P.S. (Agriculture, Ecosystems and Environment, 2005)
Field trials were conducted on Amazonian Dark Earth soils in the Manaus region, Amazonas, Brazil to assess the composition and impact of weedy vegetation on maize yield. Soil fertility among the Dark Earth varied considerably with differences largely attributable to past-use history. Consequently, maize yield and weed pressure varied among field locations, reflecting these differences in soil fertility in addition to differences in weed reservoirs such as seedbanks. Maize yield in weeded plots was as much as 63 times greater on Dark Earth (0.55 t ha-1) than on corresponding adjacent soil (0 t ha-1), and location averages varied from 0 to 3.15 t ha-1 for Dark Earth. The percentage ground cover of weeds in weedy plots was up to 45 times greater on Dark Earth (65-99%) than on corresponding adjacent soil (2-89%), and species richness was up to 11 times greater on Dark Earth (4-14 species) than corresponding adjacent soil (1-8 species). The relative proportion of annual and leguminous weeds was 32 and 17% greater, respectively, on Dark Earth than adjacent soil, and vegetative sprouting of plants was more common on sites that had been used less intensively in the past. In general, a similar weed community was observed on the different Dark Earth sites, including many species typically associated with environments that have been highly disturbed by human activities, such as Cyperus spp., Phyllantus niuri, and Croton lobatus. Seedlings from a greater number of species emerged from forested Dark Earth seedbanks (2.1 per flat) than from forested adjacent soil (1.2 per flat). The total number of emerged seedlings was greater for Dark Earth seedbanks (9.1 per flat, 1,365 m-2) than adjacent soil (2.2 per flat, 330 m-2), however the species observed were not likely to be problematic for cropping. © 2005 Elsevier B.V. All rights reserved.
Keywords: Crop Yield; Seed Bank; Soil Fertility; Tropical Soils; Weed; Amazonas; Brasil; Manaus; South America; Western Hemisphere; World; Croton Lobatus; Cyperus; Derris Amazonica; Zea Mays